Design and Development of Alignzen - Posture Checker: A Prototype Application for Posture Assessment Based on Postural Grid - Devina, Christina Natalia; Mustikasari, Nina; Pambudi, Restu Arya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
This study aims to design and develop a prototype of the Postural Grid application that utilizes Artificial Intelligence technology for rapid and accurate posture analysis. With the increasing prevalence of posture-related issues due to a sedentary lifestyle and intensive gadget use, the need for an accessible and effective tool for posture monitoring has become more urgent. The method used in this research is a prototyping approach that allows for software development through iterations based on user feedback. The results of this study indicate that the developed application can provide accurate and real-time posture assessments, which align with manual measurements by experts. This application is designed for the Android operating system and has been tested through several stages, from internal testing to open testing, to ensure its functionality and effectiveness. The use of this application is expected to assist individuals and health professionals in detecting and correcting imbalanced posture, thereby contributing to improved quality of life and physical well-being. Challenges that remain include improving accuracy under various environmental conditions and accounting for anatomical variability among users. Therefore, further research is necessary to refine this application for broader implementation in modern physiotherapy practices.